A comparison of pregnancy outcomes after second-trimester amniocentesis between cases with penetration of the placenta and nonpenetration. (2nd December 2021) - Chaksuwat, Pakorn; Wanapirak, Chanane; Piyamongkol, Wirawit; Sirichotiyakul, Supatra; Tongprasert, Fuanglada; Srisupundit, Kasemsri; Luewan, Suchaya; Traisrisilp, Kuntharee; Jatavan, Phudit; Tongsong, Theera
Abstract: Objective: To compare the fetal loss rate associated with second-trimester amniocentesis between the procedures with penetration and nonpenetration of the placenta, as a primary outcome and to compare the rates of adverse pregnancy outcomes including preterm birth, fetal growth restriction and low birth weight, as secondary outcomes. Method: A retrospective cohort study was conducted on women undergoing second-trimester amniocentesis. Our prospective database of amniocentesis, from January 1989 to December 2018, was accessed to retrieve the records meeting the inclusion criteria consisting of singleton pregnancies, gestational age of 16–22 weeks, and known obstetric outcomes. The patients were categorized into two groups: placental penetration and nonpenetration. The rates of fetal loss, including abortion (<24 weeks of gestation) and fetal death in utero (>24 weeks of gestation), and other adverse pregnancy outcomes were compared between the two groups. Results: A total of 21, 566 procedures were performed during the study period. Of them, 8601 were excluded due to chromosomal/structural abnormalities, various underlying medical diseases and incomplete data or unavailability of final outcomes. Finally, 12, 965 cases were available for analysis including 4692 (36.2%) in the group of placental penetration and 8273 (63.8%) in the group of nonpenetration. The abortion rate after amniocentesis trended to be increased in the placental penetration group (0.6 versus 0.4%, p  = .064; RR: 1.60, 95%CI 0.97-2.64). Likewise, the fetal loss rate trended to be increased in the placental penetration group (1.0 versus 0.7%, p  = .121; RR: 1.35 95%CI 0.92–1.98). Interestingly, preterm birth rate was significantly increased in the placental penetration group (13.8 versus 12.6%, p  = .043; RR: 1.10 95%CI 1.00–1.20). Conclusion: Fetal loss rate was slightly increased, but not statistically significant, among the procedures with placental penetration. However, penetration of the placenta was slightly but significantly associated with an increase in rates of preterm birth.